Health and wellness monitoring of elderly people using intelligent sensing technique - Arshad, Atika; Khan, Sheroz; Alam, A.H.M Zahirul; Tasnim, Rumana; Boby, Rounakul Islam (IEEE, 2016)
The work aims in creating a monitoring system for the elderly population intended to be used in the bedroom. The sensors selected can measure the sleep pattern and selected vital signals. This particular sensor was preferred as a result of its simplicity in integration, cost-effectiveness, and reliability. The suggested work is shown to be in the form of embedded sensors integrated in the bedroom. An alarm system has also been included in the bedroom design to assist the elderly to request for help during an emergency situation. Bed sensors are installed under the bed sheets to detect the sleeping pattern of the elderly person. Furthermore, humidity and ambient temperature sensors are also implemented in the design to constantly monitor their vital health conditions. Thus, the bedroom health and wellness monitoring system will allow an elderly person to stay independently in their own home in a secured environment.